Seismic response of precast and IBS buildings under earthquake attacks - Hamid, N. H.; Azmi, I. F.; Haryati, Awang (IOP Publishing Ltd., 2019)
Poor performances of precast buildings during earthquakes were due to inadequate connections between the structures components, insufficient seating and anchorage and poor workmanship and quality materials used. It is important to investigate their seismic performance by conducting experimental work, analyzing the data and modelling them using nonlinear time history analysis of the earthquakes. Three types' structural components of precast structures and Industrialized Building System (IBS) were designed, constructed, tested, analyzed and modelling in this chapter. There structural components are precast shear-key wall panel, beam-column joints and tunnel form building system. All these specimens were tested under in-plane lateral cyclic loading. The seismic performance parameters such as lateral strength capacity, stiffness, ductility and equivalent viscous damping were evaluated using the measured hysteresis loops from experimental work. The findings from this research work can be implemented and enforced by government and local authorities to pay special attention to joint detailing of precast structures components while constructing the precast buildings. The design concepts and detailing of the jointing precast structural components contribute significantly to the overall seismic performance of precast buildings under earthquakes excitations. A lot of structural damages occurred during earthquakes due to not using the current seismic code of practice and poor detailing especially at the jointing system.